COMPETENCES OF SOCIAL WORKERS FOR WORK WITH YOUTH: CASE ANALYSIS - Merfeldaitė, Odeta; Dilytė, Justina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Article reveals competences of social workers for work with youth based on the case analysis of social workers dealing with youth problems. It provides the content of social workers‘ competences, peculiarities of social work with youth from the professional point of view. Practical experience of social workers working with youth is interpreted as a reflection of professional activity of social workers which highlights the competences of social workers solving youth problems.  The aim of the article is to evaluate competences of social workers working with youth. The research strategy was based on the perspective of constructivism, research applied a targeted – partially structured interview data collection method. The research revealed strengths of social workers working with youth: development of trust-based professional relationship, ability to work with a group of young people, empathy, ability to take the initiative, and ability to flexibly and creatively respond to situations. Yet some weaknesses of social workers solving youth problems have been identified: understanding the role and professional restrictions of social worker and problem solution skills.